A Maryland Genealogical Study - O'Daniel, Very Reverend Victor Francis O.P., S.T.M., Litt.D.
Genealogical Study of Reverend John C. Fenwick O.P. and his relationship to Bishop Edward Dominic Fenwick O.P.
Contains one photograph of Tombstone of Fr. John C. Fenwick, O.P., S.T.Lr.